Wektor poetycki w biografiach artystów: Olga Boznańska, Wojciech Weiss, Jerzy Tchórzewski - Grodecka, Aneta (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
Starting from the contemporary trends in biography and referring to findings in the field of anthropology of writing and new materialism, the author analyzes poetic forms created in painting studios. She considers the works of O. Boznańska, W. Weiss and T. Tchórzewski as poetic manifestations of the literary practice of everyday life, a type of poeticised documents. The presence of poetry in artists’ lives is multi-faceted: loose pages preserved in a scrapbook, entries in a journal and autonomous works printed in the press, hence their role in creative biography is different. The common ground is a syncretic perception of creativity; the preserved texts co-create a kind of artistic site where the boundaries between the publication, the exhibition and the project performance blur, requiring special editing operations.